Effects of Substituents on the Electrocatalytic Activity of Cobalt Phthalocyanines when Conjugated to Graphene Quantum Dots. Issue 11 (11th August 2017) - Centane, Sixolile; Achadu, Ojodomo J.; Nyokong, Tebello
Abstract: We report on the π–π interactions between graphene quantum dots (GQDs) and the following cobalt phthalocyanine derivatives: cobalt monocarboxyphenoxy phthalocyanine (complex1 ), cobalt tetracarboxyphenoxyphthalocyanine (complex2 ), and cobalt tetraaminophenoxy phthalocyanine (complex3 ). The conjugates (conj) with GQDs are represented as1 @GQDs(conj), 2 @GQDs(conj) and3 @GQDs(conj), respectively. The resulting phthalocyanine/GQDs conjugates were adsorbed on containing a glassy carbon electrode (GCE) using the drop and dry method. We explore the electrochemical properties of phthalocyanines functionalized with both electron withdrawing groups and electron donating groups when non‐covalently linked to the π‐electron rich graphene quantum dots. GCE/3, GCE/2 @GQDs(conj) and GCE/1 @GQDs(conj) had the lowest limits of detection (LOD). Sequentially modified electrodes showed less favourable detection limits compared to the conjugates. Abstract :